Endovascular placement of an extraluminal arterial bypass graft – in vitro feasibility study. Issue 6 (1st November 2016) - Zimmermann, Markus; Pfeffer, Jochen; Na, Hong-Sik; Liebl, Martin; Schulze-Hagen, Maximilian; Kuhl, Christiane K.; Isfort, Peter; Bruners, Philipp
Abstract: Purpose: A novel approach for arterial bypass grafting using exclusively endovascular techniques was established in-vitro in a phantom model. Material and methods: The experimental setting consisted of a gel-wax phantom with two embedded parallel fluid-filled silicon tubes simulating the superficial femoral vessels. Through an 8-French sheath, a re-entry catheter (OUTBACK ®, Cordis) was placed in the simulated artery and used to puncture the vascular wall. Then a 0.014-inch guide wire was advanced into the extravascular space. With the curved needle of the re-entry catheter, the guide wire was steered on a course parallel to the vessel wall in the extravascular space for 5-10 cm. At the desired reentry site, the re-entry catheter was used to puncture the vascular wall again in order to regain access to the endovascular space. Once the tip of the guide wire had safely been placed in the vascular lumen, a self-expandable stent graft (VIABAHN ® GORE ® ) was deployed to complete the extraluminal bypass. Results: Endovascular placement of an extraluminal bypass was successfully achieved in 20 attempts. The mean duration of the procedure amounted to 14:58 (minutes: seconds) (SD ± 3:56). Conclusions: This in-vitro study suggests that endovascular placement of an extraluminal arterial bypass graft is technically feasible.